New Briarane Diterpenoids from Taiwanese Soft Coral Briareum violacea - Liaw, Chia-Ching (MDPI, 2014)
Ten new briarane diterpenoids, briaviolides A–J (1–10), together with six known briaranes, solenolides A and D, excavatolide A, briaexcavatolide I, 4β-acetoxy-9-deacetystylatulide lactone and 9-deacetylstylatulide lactone, were isolated from the Taiwanese soft coral, Briareum violacea. Their structures were determined on the basis of spectroscopic data ((1)H- and (13)C-NMR, (1)H–(1)H COSY, HSQC, HMBC and NOESY), HR-MS and chemical methods. The absolute configuration of briaviolide A (1) was determined by X-ray crystallographic analysis. Compounds 5, 9 and derivative 11 showed moderate inhibitory activities on superoxide-anion generation and elastase release by human neutrophils in response to N-formyl-methionyl-leucyl-phenylalanine/Cytochalasin B (fMLP/CB).